Adsorção de fósforo e chumbo em ferrihidritas-2 linhas coprecipitadas com Cr(III), Zn(II), Ni(II), Pb(II) e Al(III) - Vilar, Cesar Crispim (2013)
This work was carried out to study the changes on chemical and mineralogical properties of ferrihydrites coprecipitaded with metals and their phosphorus and lead adsorption behavior. For this purpose, samples of pure (F0) and two metal concentration (Cr(III), Zn(II), Ni(II), Pb(II) and Al(III)) were synthesized. A general introduction to the topic under study is presented in Chapter 1. Then, in Chapter 2, the data obtained during the synthesis and characterization of minerals. Moreover, in Chapters 3 and 4 the results of the adsorption and modeling experiments are presented for phosphorus and lead, respectivelly. Changes in ferrihydrite structure were studied by thermal analysis and X-ray diffraction. Phosphorus and lead sorption experiments with varying pH, ionic strength and initial concentration of phosphorus were performed. Empirical (Langmuir and Freudlich) and surface complexation models (Constant Capacitance Model - MCC and modified Triple Layer Model - TLM) were adjusted to data. Ferrihydrites were coprecipitate with cations and metal concentrations ranged from 0.3 to 11 mol%. The order of increasing metal content in the lower initial metal content was: F6,4Ni > F5,3Al > F4,2Zn > F3,9Cr > F0,3Pb. For samples with higher initial metal content the order changed to: F11Al > F9,8Zn > F8,4Ni > F7,6Cr > F0,9Pb. The ability of metals to substitute Fe was determined by their ionic radius and solubility. Lead coprecipitaded samples presented lower position of reflexes and lower crystallinity values by X-rays analysis. Differential scanning calorimetry showed the evolution of ferrihydrite to hematite at 371ºC for F0, and for all other was greater than 449°C. The sample that showed the highest phosphorus adsorption capacity was F0,9Pb and the lowest F0. These minerals desorbed also the smaller and larger amount of phosphorus. The sorption experiments varying the pH showed similar behavior for all ferrihydrite samples. The MCC adjusted to phosphorus adsorption data varying the pH and ionic strength, being better for the highest ionic strength. The monodentate complexes were selected in this model. The TLM did not fit to phosphorus adsorption data. Lead adsorption was higher at pH values above 5.5. MCC fit to the data using only one inner sphere bidentate complex. TLM presented a better fit, probably because it was possible to fit a larger number of species (1 bidentate, 1 monodentate 1 and 1 outer sphere complex). Coprecipitation of ferrihydrite with different metals did not affect the fit of the surface complexation models, except to lead ferrihydrites that interfere at lead adsorption experiments.